Glass cloth, prepreg, printed circuit board, and surface treatment liquid
By performing high-temperature degreasing on the glass cloth and then surface treatment with a specific silane coupling agent, the problems of increased dielectric loss tangent and white spots were solved, achieving low dielectric loss tangent and excellent dielectric properties, suitable for prepregs and printed circuit boards.
Patent Information
- Application Number
- CN202510474574.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-17
- Filing Date
- 2025-04-16
- Publication Date
- 2025-10-24
AI Technical Summary
Existing technologies are insufficient to effectively suppress the time-dependent increase of the dielectric loss tangent of glass cloth, and surface treatment may lead to an increase in the dielectric loss tangent and white spot problems.
Glass cloth is treated with a surface treatment agent containing silane coupling agent. The molecular structure of the silane coupling agent meets specific conditions. After high-temperature degreasing, the surface treatment reduces the dielectric loss tangent and inhibits its increase over time, while controlling the appearance of white spots.
This method achieves low dielectric loss tangent of glass cloth, suppresses the time-dependent increase of dielectric loss tangent, reduces white spots, and improves dielectric properties and interfacial adhesion.
Smart Images

Figure CN120830252A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to glass cloth, prepreg, printed circuit board, and surface treatment liquid, etc. BACKGROUND
[0002] Currently, high performance of information terminals such as smartphones and high speed communication represented by 5G communication are being promoted. With this, low dielectric constant and low dielectric loss tangent of insulating materials used in printed circuit boards for high speed communication in order to reduce transmission loss are being significantly promoted, and in addition, higher levels of insulating reliability than ever before are also being sought.
[0003] Examples of insulating materials for printed circuit boards for high speed communication are reported in Patent Documents 1 and 2. Specifically, in Patent Documents 1 and 2, a low dielectric thermosetting resin (hereinafter collectively referred to as “matrix resin”) which is crosslinked by radical reaction of polyphenylene ether or the like modified at the end by using a vinyl group or a methacryloyloxy group, thereby undergoing curing, is impregnated into a glass cloth, and dried, thereby obtaining a prepreg. A laminate obtained by stacking the prepreg thus obtained and curing it by heating and pressing is known. The purpose of Patent Documents 1 and 2 is to obtain a laminate having a low dielectric constant and a low dielectric loss tangent, using a glass cloth having a low dielectric constant and a low dielectric loss tangent.
[0004] Here, in order to reduce the dielectric loss tangent of the glass cloth, Patent Documents 3 and 4 describe that the amount of silanol groups on the surface of the glass is reduced by heating the silica glass cloth at high temperature. In addition, Patent Document 5 describes that the silanol groups present on the surface of the glass cloth are reduced by surface treatment, and thereby the dielectric loss tangent of the glass cloth is reduced. In addition, Patent Document 6 describes a baling method of quartz glass cloth for suppressing the temporal increase in the dielectric loss tangent of the quartz glass cloth.
[0005] PRIOR ART DOCUMENTS
[0006] PATENT DOCUMENTS
[0007] Patent Document 1: International Publication No. 2019 / 065940
[0008] Patent Document 2: International Publication No. 2019 / 065941
[0009] Patent Document 3: Japanese Patent Application Publication No. 2021-63320
[0010] Patent Document 4: Japanese Patent Application Publication No. 2021-195689
[0011] Patent Document 5: Japanese Patent Application Publication No. 2020-194888
[0012] Patent Literature 6: Japanese Patent No. 7375902 SUMMARY
[0013] PROBLEMS TO BE SOLVED BY THE INVENTION
[0014] An object of the present application is to provide a glass cloth having excellent dielectric properties, which can suppress a temporal increase in dielectric loss tangent. Another object is to provide a method for producing the glass cloth and a surface treatment liquid used in the glass cloth. Further, an object of the present application is to provide a prepreg and a printed circuit board, etc., obtained using the glass cloth.
[0015] SOLUTION TO PROBLEM
[0016] Examples of embodiments of the present application are listed in the following items [1] to
[38] .
[0017] [1] A glass cloth composed of a glass yarn containing a plurality of glass filaments as warp and weft,
[0018] The glass cloth has a surface treatment agent on a surface,
[0019] The surface treatment agent contains a silane coupling agent having a molecular structure with a value calculated from the following formula (A) of 15.0 or less,
[0020] 1.10 x MaxEStateIndex + 14.6 x MaxPartialCharge - 0.0917 x SPS + 2.47 x HallKierAlpha... (A).
[0021] [2] The glass cloth according to item 1, wherein the white spots are 10 / m 2 or less.
[0022] [3] The glass cloth according to item 1 or 2, wherein the content of silicon (Si) in the glass yarn is 95.0 to 100 mass% in terms of silicon dioxide (Si02).
[0023] [4] The glass cloth according to any one of items 1 to 3, wherein the silane coupling agent contains a silane coupling agent represented by the following general formula (1).
[0024] X 4-n -Si-Y n ... (1)
[0025] (In formula (1), each X is independently an organic functional group having at least one group selected from the group consisting of an epoxy group, an amino group, and an unsaturated double bond group having radical reactivity, each Y is independently an alkoxy group, and n is an integer of 1 or more and 3 or less)
[0026] [5] The glass cloth according to item 4, wherein X in the above general formula (1) contains at least one group selected from the group consisting of an epoxy group, an amino group, an aromatic vinyl group, an acryloyl group, and a methacryloyl group.
[0027] [6] The glass cloth according to any one of items 1 to 5, wherein a dielectric loss tangent of the glass cloth at 10 GHz is 0.002 or less.
[0028] [7] The glass cloth according to any one of items 1 to 6, which has a loss on ignition value in the range of 0.01 to 0.3 mass%.
[0029] [8] The glass cloth according to any one of items 1 to 7, wherein a value calculated from the above formula (A) is 14.4 or less.
[0030] [9] The glass cloth according to any one of items 1 to 8, wherein a value calculated from the above formula (A) is 13.8 or less.
[0031]
[10] The glass cloth according to any one of items 1 to 9, wherein a value calculated from the above formula (A) is 13.5 or less.
[0032]
[11] The glass cloth according to any one of items 1 to 10, wherein the white spots are 4 / m 2 or less.
[0033]
[12] The glass cloth according to any one of items 1 to 11, wherein the white spots are 2 / m 2 or less.
[0034]
[13] The glass cloth according to any one of items 1 to 12, wherein the white spots are 0.1 / m 2 or less.
[0035]
[14] The glass cloth according to any one of items 1 to 13, wherein the white spots are 0.05 / m 2 or less.
[0036]
[15] The glass cloth according to any one of items 1 to 14, wherein the silane coupling agent has a molecular weight in the range of 250 to 1000.
[0037]
[16] The glass cloth according to any one of items 1 to 15, wherein the silane coupling agent has a molecular weight in the range of 300 to 750.
[0038]
[17] The glass cloth according to any one of items 1 to 16, wherein the silane coupling agent has a molecular weight in the range of 350 to 700.
[0039]
[18] The glass cloth according to any one of items 1 to 17, which is used for a printed circuit board.
[0040]
[19] A prepreg comprising the glass cloth according to any one of items 1 to 18, a matrix resin, and an inorganic filler.
[0041]
[20] A printed circuit board comprising the prepreg according to item 19.
[0042]
[21] An integrated circuit comprising the printed circuit board according to item 20.
[0043]
[22] An electronic device comprising the printed circuit board according to item 20.
[0044]
[23] A method for producing a glass cloth, wherein the method comprises:
[0045] a step of weaving a glass yarn comprising a plurality of glass filaments as warp and weft to obtain a glass cloth, and
[0046] a step of performing surface treatment on the glass cloth after the oil removal treatment using a surface treatment liquid containing a surface treatment agent,
[0047] the surface treatment agent contains a silane coupling agent having a molecular structure with a value of 15.0 or less calculated from the following formula (A).
[0048] 1.10 x MaxEStateIndex + 14.6 x MaxPartialCharge - 0.0917 x SPS + 2.47 x HallKierAlpha... (A)
[0049]
[24] The method for producing a glass cloth according to item 23, wherein the silane coupling agent contains a silane coupling agent represented by the following general formula (1).
[0050] X 4-n -Si-Y n ... (1)
[0051] (In formula (1), each X is independently an organic functional group having at least one group selected from an epoxy group, an amino group, and an unsaturated double bond group having radical reactivity, each Y is independently an alkoxy group, and n is an integer of 1 or more and 3 or less)
[0052]
[25] The method for producing a glass cloth according to item 23 or 24, wherein the surface treatment liquid is prepared by adding an acidic aqueous solution to a hydrolyzed solution of the silane coupling agent.
[0053]
[26] The method for manufacturing a glass cloth according to any one of items 23 to 25, wherein the surface treatment step includes:
[0054] controlling the temperature and pH of the surface treatment liquid; and
[0055] filtering the surface treatment liquid.
[0056]
[27] The method for manufacturing a glass cloth according to any one of items 23 to 26, further comprising a step of performing a fiber opening treatment on the glass cloth after the surface treatment step.
[0057]
[28] The method for manufacturing a glass cloth according to any one of items 23 to 27, further comprising a step of inspecting white spots after the surface treatment step.
[0058]
[29] A surface treatment liquid comprising a surface treatment agent containing a silane coupling agent,
[0059] the silane coupling agent has a molecular structure having a value of 15.0 or less calculated from the following formula (A).
[0060] 1.10 x MaxEStateIndex + 14.6 x MaxPartialCharge - 0.0917 x SPS + 2.47 x HallKierAlpha... (A)
[0061]
[30] The surface treatment liquid according to item 29, wherein the surface treatment liquid contains the silane coupling agent in a range of 0.20 to 1.2 mass% based on the total mass of the surface treatment liquid,
[0062] the pH of the surface treatment liquid is in a range of 2.5 to 5.5,
[0063] the surface treatment liquid contains a surfactant in a range of 0.5 to 5.0 mass% based on the total mass of the silane coupling agent.
[0064]
[31] The surface treatment liquid according to item 29 or 30, wherein the silane coupling agent contains a silane coupling agent represented by the following general formula (1).
[0065] X 4-n -Si-Y n ... (1)
[0066] (In formula (1), each X is independently an organic functional group having at least one group selected from an epoxy group, an amino group, and an unsaturated double bond group having a radical reactivity, each Y is independently an alkoxy group, and n is an integer of 1 or more and 3 or less)
[0067]
[32] The surface treatment liquid according to any one of items 29 to 31, wherein the value calculated from the above formula (A) is 14.4 or less.
[0068]
[33] The surface treatment liquid according to any one of items 29 to 32, wherein the value calculated from the above formula (A) is 13.8 or less.
[0069]
[34] The surface treatment liquid according to any one of items 29 to 33, wherein the value calculated from the above formula (A) is 13.5 or less.
[0070]
[35] The surface treatment liquid according to any one of items 29 to 34, wherein the pH of the above surface treatment liquid is in the range of 3.0 to 5.0.
[0071]
[36] The surface treatment liquid according to any one of items 29 to 35, wherein the pH of the above surface treatment liquid is in the range of 3.0 to 4.0.
[0072]
[37] The surface treatment liquid according to any one of items 29 to 36, wherein the above surface treatment liquid contains a surfactant in the range of 1.0 to 4.5 mass% based on the total mass of the above silane coupling agent.
[0073]
[38] The surface treatment liquid according to any one of items 29 to 37, wherein the above surface treatment liquid contains a surfactant in the range of 1.5 to 4.0 mass% based on the total mass of the above silane coupling agent.
[0074] Effects of the Invention
[0075] According to the present application, a glass cloth having excellent dielectric properties and capable of suppressing the temporal increase in dielectric loss tangent can be provided. In addition, a method for manufacturing the above glass cloth and a surface treatment liquid used in the above glass cloth can be provided. Furthermore, a prepreg and a printed circuit board, etc. obtained using the above glass cloth can be provided. BRIEF DESCRIPTION OF DRAWINGS
[0076] Figure 1 is a diagram for explaining white spots.
[0077] EXPLANATION OF REFERENCE NUMERALS
[0078] P: white spot DETAILED DESCRIPTION
[0079] Hereinafter, the embodiments of the present application will be described. The present application is not limited only to the following embodiments, and various modifications can be made within the scope of the gist thereof.
[0080] In this specification, when there are multiple structures represented by the same symbol in the same formula, as long as it is not otherwise specified, the structure can be selected independently of each other, and in addition, they can be the same or different from each other. When there are multiple structures represented by the same symbol in different formulas, as long as it is not otherwise specified, the structure can be selected independently of each other, and in addition, they can be the same or different from each other. In this specification, as long as there is no special record, various determinations are carried out according to the method described in the embodiment. In this specification, the upper limit or lower limit in the numerical range of stage-by-stage recording can be replaced by the upper limit or lower limit in the numerical range of corresponding other stage-by-stage recordings, and then, can be replaced by the corresponding value recorded in the embodiment.
[0081] In this specification, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the function of the process is achieved. In the drawings, the scale, shape, and length may be exaggerated for greater clarity.
[0082] Glass Cloth
[0083] The glass cloth of the present application is a glass cloth woven from glass yarn, for example, a glass cloth composed of glass yarn containing a plurality of glass filaments as warp and weft yarns. The surface of the glass cloth has a surface treatment agent, and the silane coupling agent contained in the surface treatment agent has a molecular structure with a value of 15.0 or less as determined by the following formula (A).
[0084] 1.10×MaxEStateIndex+14.6×MaxPartialCharge-0.0917×SPS+2.47×HallKierAlpha…(A)
[0085] According to the present application, a glass cloth having excellent dielectric properties and capable of suppressing the time-dependent increase in dielectric loss tangent can be provided. The glass cloth of the present application is suitable as a component material for manufacturing prepregs, printed circuit boards, integrated circuits, electronic devices, and the like. Preferably, the dielectric loss tangent of the glass cloth can be further reduced compared to the prior art described in Patent Documents 1 to 6. Furthermore, preferably, the time-dependent increase in dielectric loss tangent of the glass cloth can be suppressed without using the method described in Patent Document 6 of bundling the quartz glass cloth using a predetermined method.
[0086] As a result of intensive studies by the present inventors, attention was paid to a glass cloth which is subjected to surface treatment after being subjected to heat and oil removal at a high temperature. The present inventors first found that, in a glass cloth which is subjected to surface treatment using a silane coupling agent having a molecular structure for which the value calculated from the above formula (A) is 15.0 or less after being subjected to heat and oil removal at a high temperature, the dielectric loss tangent of the glass cloth is low, and the temporal increase in the dielectric loss tangent of the glass cloth can be suppressed. The reason for this is not limited by theory, but it is believed that this is because the silane coupling agent covers the surface of the glass yarn, and thus moisture present in the storage environment is not easily adsorbed. Therefore, for example, even if special bundling is not performed, the temporal increase in the dielectric loss tangent of the glass cloth can be suppressed. The technical meanings of the respective parameters and the like are described later.
[0087] The silane coupling agent is generally applied to the glass cloth in the form of a mixture thereof with a solvent, and in this case, from the viewpoint of reducing the environmental burden, it is preferable to use water as the solvent. However, it was found that a silane coupling agent for which the value calculated from formula (A) is 15.0 or less is highly hydrophobic, and the dispersibility and / or compatibility in water is significantly poor, and thus "white spots" caused by the surface treatment agent are easily generated on the surface of the glass cloth. The white spots sometimes hinder the interfacial adhesion of the glass cloth to a resin, and thus it is preferable to provide a glass cloth which suppresses white spots and has a value lower than the dielectric loss tangent of a bulk glass.
[0088] According to one preferred mode of the present application, even if a surface treatment agent (for example, a silane coupling agent which is highly hydrophobic) which lacks dispersibility and / or compatibility in water, that is, which is highly hydrophobic, is stably dispersed in water, white spots can be suppressed. In this case, it is easy to provide a glass cloth having a lower dielectric loss tangent, and in addition, even if special bundling is not performed, it is easier to suppress the temporal increase in the dielectric loss tangent of the glass cloth. In addition, it is easy to provide a glass cloth which can provide a resin substrate having excellent resistance to solder heat.
[0089] 〔Dielectric Loss Tangent〕
[0090] (Dielectric Loss Tangent of Glass Cloth)
[0091] The dielectric loss tangent of the glass cloth at 10 GHz according to the present application is preferably 0.0020 or less. If this is the glass cloth, a prepreg and a printed circuit board which can achieve an improvement in dielectric properties can be provided. From the viewpoint of achieving an improvement in dielectric properties, the dielectric loss tangent of the glass cloth at 10 GHz is preferably 0.0015 or less, 0.0010 or less, 0.0007 or less, 0.0006 or less, 0.0005 or less, 0.0004 or less, 0.0003 or less, or 0.0002 or less. The dielectric loss tangent of the glass cloth can exceed 0.
[0092] (Method for measuring dielectric loss tangent of glass cloth)
[0093] The dielectric loss tangent at 10 GHz of the glass cloth according to the present application is measured by a method using a split post resonator (a method using a resonance method), specifically, the method described in the examples. According to this method, the measurement is easily and simply performed with good accuracy, compared to the existing measurement method of evaluating the dielectric properties by producing a substrate as a measurement sample. Without being limited to the theory, this is because: the resonance method is suitable for evaluation in a high frequency region, and in particular, for evaluation of low-loss materials. As a method for evaluating dielectric properties other than the resonance method, for example, a lumped constant method and a reflection transmission method are known. However, in the lumped constant method, it is necessary to sandwich a measurement sample with two electrodes to form a capacitor, and thus, there is a problem that the operation becomes complicated. In addition, in the reflection transmission method, when evaluating low-loss materials, the influence of the matching characteristics of the port is strongly exhibited, and thus, there is a problem that it is difficult to evaluate the dielectric loss tangent of the measurement sample with high accuracy. In summary, by the method based on the resonance method, specifically, the method described in the examples, the dielectric loss tangent of the glass cloth is easily and simply measured with good accuracy.
[0094] The measurement device for measuring the dielectric properties of the glass cloth used in the printed circuit board, particularly the glass cloth used in the printed circuit board for high-speed communication, preferably has a prescribed measurable range. For example, with respect to the dielectric constant (Dk) and the dielectric loss tangent (Df), the measurement device preferably has a measurable range of Dk = 1.1 to 50 and Df = 1.0 x 10 -6 to 5.0 x 10 -1 , more preferably a measurable range of Dk = 1.5 to 10 and Df = 1.0 x 10 -5 to 5.0 x 10 -1 , further preferably a measurable range of Dk = 2.0 to 5 and Df = 5.0 x 10 -5 to 1.0 x 10 -2 .
[0095] In addition, the frequency that can be measured by the measurement device for measuring the dielectric properties is preferably 10 GHz or more. If the frequency that can be measured is 10 GHz or more, it is easy to evaluate the properties in the frequency band region, particularly the properties in the frequency band region that are assumed when actually used as the glass cloth for the printed circuit board for high-speed communication, and the like.
[0096] The measurement area of the dielectric properties is preferably 10 mm 2 or more, more preferably 15 mm 2 or more, further preferably 20 mm 2The above. According to this, it is easy to improve the reliability of the obtained measurement result, and thus it is easy to appropriately determine whether the obtained measurement result is within the range of the reference value set in advance.
[0097] The thickness of the sample to be measured is preferably 3 μm to 300 μm, more preferably 5 μm to 200 μm, and further preferably 7 μm to 150 μm.
[0098] (bulk dielectric loss tangent)
[0099] The bulk dielectric loss tangent at 10 GHz of the glass cloth of the present application is measured by using a split post resonator method (a method using a resonance method), specifically, the method described in the examples, with respect to the glass raw material constituting the glass cloth. Here, the glass raw material can be, for example, glass yarn, glass filament, and glass seed, etc.
[0100] The bulk dielectric loss tangent at 10 GHz is preferably 0.002 or less, more preferably 0.0015 or less, further preferably 0.001 or less, still further preferably 0.0005 or less, and particularly preferably 0.0004 or less. According to this, the excellent dielectric properties are more easily exhibited.
[0101] [Glass Yarn]
[0102] The glass yarn can be formed of a plurality of glass filaments. By weaving the glass yarn as warp and weft, a glass cloth can be produced.
[0103] [Mean Filament Diameter]
[0104] The mean filament diameter of the glass filament is preferably 2.5 μm to 9.0 μm, more preferably 2.5 μm to 7.5 μm, further preferably 3.5 μm to 7.0 μm, still further preferably 3.5 μm to 6.0 μm, and particularly preferably 3.5 μm to 5.0 μm.
[0105] [Insertion Density]
[0106] The insertion density of the glass yarn (warp and weft) constituting the glass cloth is preferably 10 to 120 strands / inch (= 10 to 120 strands / 25.4 mm), more preferably 40 to 100 strands / inch, and further preferably 45 to 90 strands / inch.
[0107] [Weight per Unit Area]
[0108] The weight per unit area of the glass cloth is preferably 8 to 250 g / m 2 , more preferably 8 to 100 g / m 2 , and further preferably 8 to 80 g / m2 , and particularly preferably 8 to 50 g / m 2 .
[0109] (Glass Type)
[0110] In the past, the glass cloth used in prepreg (laminate) can use a glass raw material generally called E glass (alkali-free glass). On the other hand, the glass cloth of the present application can use a glass raw material such as L glass, NE glass, D glass, L2 glass, T glass, silica glass, and quartz glass. From the viewpoint of excellent dielectric properties, it is preferable to use a glass raw material such as L glass, L2 glass, silica glass, and quartz glass, and particularly preferably silica glass and quartz glass. In addition, from the viewpoint of improving the dimensional stability of the laminate containing the glass cloth, it is preferable to use a glass raw material such as S glass, T glass, silica glass, and quartz glass, and particularly preferably silica glass and quartz glass.
[0111] In the glass yarn constituting the glass cloth, the Si content, calculated as SiO2, is preferably 95.0 to 100 mass% or 99.0 to 100 mass%, more preferably 99.5 to 100 mass%, and further preferably 99.9 to 100 mass%. The SiO2 content of the glass yarn constituting the glass cloth is particularly preferably more than 99.9 mass%. If the Si content is 95.0 mass% or more, it is easy to ensure the dielectric properties of the glass cloth and the dimensional stability of the laminate.
[0112] (Weaving Structure)
[0113] As the weaving structure of the glass cloth, weaving structures such as plain weave, basket weave, satin weave, and twill weave can be cited, and more preferably a plain weave structure.
[0114] (Surface Treatment Agent)
[0115] The glass cloth has a surface treatment agent on the surface. The surface treatment is performed by, for example, a method using a surface treatment liquid containing a surface treatment agent. Details are described later.
[0116] It has been known that if a general surface treatment agent (for example, a general silane coupling agent) is used, the dielectric loss tangent of a glass cloth increases due to surface treatment, and in addition, the dielectric loss tangent of the glass cloth increases over time. In this regard, the present inventors have found as a result of their studies that by surface-treating the glass surface with a surface treatment agent (for example, a silane coupling agent) having high hydrophobicity, it is possible to reduce the increase in the dielectric loss tangent of the glass cloth due to surface treatment, and in addition, moisture present in the storage environment is less likely to be adsorbed to the glass surface, as a result of which the dielectric loss tangent of the glass cloth is easily inhibited from increasing over time, even if it is not a special bale form that is moisture-proof.
[0117] The "surface treatment agent having high hydrophobicity (silane coupling agent having high hydrophobicity)" in the present application means that when an aqueous solution obtained by mixing an aqueous acetic acid solution at 0.3 mass% with the surface treatment agent (silane coupling agent) at a concentration of 0.8 mass% is stirred at room temperature of 25°C for 3 hours, the surface treatment agent (silane coupling agent) assumes a state of being not uniformly dispersed as an emulsion or a state of being not dissolved in the aqueous solution. The state of being not uniformly dispersed as an emulsion or the state of being not dissolved means, for example, a state in which the surface treatment agent (silane coupling agent) is separated in the aqueous solution in the form of oil droplets and oil films.
[0118] (Silane coupling agent)
[0119] In the present application, the surface treatment agent preferably contains a silane coupling agent. That is, the glass yarn (also including glass filaments) constituting the glass cloth is preferably surface-treated with a silane coupling agent.
[0120] The glass cloth described in the present application is surface-treated with a silane coupling agent having a value calculated using the following formula (A) of 15.0 or less.
[0121] 1.10 x MaxEStateIndex + 14.6 x MaxPartialCharge - 0.0917 x SPS + 2.47 x HallKierAlpha... (A)
[0122] MaxEStateIndex, MaxPartialCharge, SPS, and HallKierAlpha included in formula (A) can be calculated by the method described in the examples. Specifically, they can be calculated by using open source software called "RDKit".
[0123] MaxEStateIndex used in formula (A) is a value indicating the electronic property of an atom calculated from the charge of the atom, the number of bonds, and the like, and it can be considered that if the MaxEStateIndex value of an atom is high, the polarity of a molecule, the hydrogen bonding ability becomes high. In addition, it can be considered that MaxPartialCharge indicates the partial charge of a molecule, and the greater the value, the greater the dipole moment within the molecule, and the more easily polarized. In order to easily obtain excellent dielectric properties and easily suppress the temporal increase in the dielectric loss tangent, the lower the values of MaxEStateIndex and MaxPartialCharge are more preferable. The more the glass sheet is covered with a silane coupling agent that is strongly polarized, the more moisture in the air is adsorbed, and it is difficult to suppress the temporal increase in the dielectric loss tangent of the glass cloth without special packaging.
[0124] In addition, SPS used in formula (A) is an empirical scoring system for expressing the spatial complexity of a compound in a uniform pattern and with a highly granular scale in terms of intermolecular rating and contrast, and shows a tendency that the greater the value, the less the steric hindrance. In addition, Hall Kier Alpha refers to a topological index indicating the steric hindrance of a molecule, and the greater the value, the higher the steric hindrance. According to their results, it shows the tendency that the more the surface of the glass cloth is treated with a silane coupling agent having high steric hindrance, the more moisture in the air is easily adsorbed. This is because the higher the steric hindrance of the silane coupling agent, the more difficult it is to uniformly chemically modify the glass surface, and the more easily the silane coupling agent layer is sparse, and thus, moisture in the air is easily adsorbed, and the temporal increase in the dielectric loss tangent of the glass cloth is easily induced.
[0125] From the viewpoint of easily obtaining excellent dielectric properties and suppressing the temporal increase in the dielectric loss tangent, the value calculated from formula (A) is preferably 14.9 or less, more preferably 14.8 or less, further preferably 14.7 or less, more further preferably 14.6 or less, particularly preferably 14.4 or less, 14.2 or less, 14.0 or less, or 13.8 or less. The lower limit of the value calculated from formula (A) is not particularly limited, and can be more than 0, 1 or more, 5 or more, or 10 or more.
[0126] The surface treatment agent preferably contains, for example, a silane coupling agent represented by the following formula (1).
[0127] X 4-n -Si-Y n …(1)
[0128] (In formula (1), each X is independently an organic functional group having at least one group selected from the group consisting of an epoxy group, an amino group, and an unsaturated double bond group having radical reactivity, each Y is independently an alkoxy group, and n is an integer of 1 or more and 3 or less.)
[0129] By including the silane coupling agent in the surface treatment agent, it is easier to suppress the increase in the dielectric loss tangent of the glass cloth over time.
[0130] From the viewpoint of easily improving adhesion to a resin, X in formula (1) is more preferably an organic functional group having at least one group selected from the group consisting of an epoxy group, an amino group, an aromatic vinyl group, an acryloyl group, and a methacryloyl group in its structure. In addition, as the organic functional group, each is independently preferably at least one selected from the group consisting of an aromatic group, and an aliphatic group that is optionally saturated or unsaturated, optionally straight-chain or branched, with or without a cyclic structure, with or without a heteroatom, and combinations thereof, for example. The total number of carbon atoms of X can be preferably 3 to 20, 5 to 18, 6 to 16, or 7 to 14.
[0131] As to the above Y, as an alkoxy group, from the viewpoint of stability of the surface treatment performed on the glass cloth, an alkoxy group having 1 to 5 carbon atoms (1, 2, 3, 4, or 5 carbon atoms) is preferred.
[0132] As the silane coupling agent included in the surface treatment agent, the silane coupling agent represented by the above formula (1) can be used alone or in a plurality. For example, two or more silane coupling agents different in the above X can be used in combination.
[0133] As the silane coupling agent represented by general formula (1), for example, the following substances and the like can be mentioned.
[0134] 3,6-divinyl-1-(trimethoxysilyl)naphthalene represented by the following formula,
[0135]
[0136] [4-[2-(trimethoxysilyl)ethyl]phenyl]methyl-2-propenoate represented by the following formula,
[0137]
[0138] 4-(trimethoxysilyl)phenyl-2-propenoate represented by the following formula,
[0139]
[0140] N-vinyl-N-(2-oxiranylmethoxy)-3-(trimethoxysilyl)-1-propanamine represented by the following formula,
[0141]
[0142] 1-vinyl-4-[3-(trimethoxysilyl)propoxy]benzene represented by the following formula,
[0143]
[0144] 4-[2-(trimethoxysilyl)ethyl]aniline represented by the following formula,
[0145]
[0146] [Bicyclo[2.2.1]hept-5-en-2-yl]triethoxysilane represented by the following formula,
[0147]
[0148] 4-[[4-[3-(trimethoxysilyl)propoxy]phenyl]sulfonyl]phenyl-2-methyl-2-acrylate represented by the following formula,
[0149]
[0150] 6-[[[3-(Trimethoxysilyl)propyl]amino]carbonyl]-2-naphthylene-2-methyl-2-propenoate represented by the following formula,
[0151]
[0152] 2-Acrylic acid, 2-methyl-, 2-[(trimethoxysilyl)methyl]-1,3-propanediyl ester represented by the following formula,
[0153]
[0154] Diethoxy(methyl)[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane represented by the following formula,
[0155]
[0156] Ethoxy(dimethyl)[3-(oxiran-2-ylmethoxy)propyl]silane represented by the following formula,
[0157]
[0158] [2-(bicyclo[2.2.1]hept-5-en-2-yl)ethyl](trimethoxy)silane represented by the following formula,
[0159]
[0160] N-2-propen-1-yl-N-[3-(trimethoxysilyl)propyl]-2-oxiranylmethylamine represented by the following formula,
[0161]
[0162] N1-vinyl-N1-(phenylmethyl)-N2-[3-(trimethoxysilyl)propyl]-1,2-ethanediamine represented by the following formula,
[0163]
[0164] 1-[trans-4-[4-(3-methylbutyl)phenyl]cyclohexyl]-2-(trimethoxysilyl)ethyl-2-methyl-2-propenoate represented by the following formula.
[0165]
[0166] The silane coupling agent that can be used can be appropriately adjusted according to the matrix resin or the like used in the resin substrate. Of course, a silane coupling agent having a value of 15.0 or less according to the above formula (A) can be used in combination with a silane coupling agent other than the silane coupling agent having a value of 15.0 or less according to the above formula (A). On the other hand, it is preferable to use two or more kinds of silane coupling agents having a value of 15.0 or less according to the above formula (A) and different molecular weights. By using two or more kinds of silane coupling agents having different molecular weights, the treatment agent density of the glass surface is easily increased, and as a result, there is a tendency that the reactivity with the matrix resin is further increased.
[0167] (Molecular weight of silane coupling agent)
[0168] The molecular weight of the surface treatment agent, for example, the molecular weight of the silane coupling agent, is preferably 250 to 1000, more preferably 270 to 800, further preferably 300 to 750, and particularly preferably 350 to 700. Note that when two or more kinds of surface treatment agents (for example, silane coupling agents) are used, it is preferable that the weighted average of the molecular weight with the mass of each surface treatment agent as the weight be within the above range, and more preferably the molecular weight of each of the plurality of surface treatment agents used be within the above range. For example, when a silane coupling agent having a molecular weight of 300 and a silane coupling agent having a molecular weight of 500 are used at 0.5 mass% and 1.0 mass%, respectively, the weighted average can be calculated as follows.
[0169] Weighted average
[0170] = 300 x 0.5 ÷ (0.5 + 1.0) + 500 x 1.0 ÷ (0.5 + 1.0)
[0171] = 433
[0172] (Average fiber opening degree of glass cloth)
[0173] The average degree of opening of the glass cloth is preferably 35% or more, or more than 36%, more preferably more than 38%, further preferably more than 40%, more than 45%, more than 50%, more than 52%, or more than 55%, particularly preferably more than 57%. If the average degree of opening of the glass cloth is 35% or more, it is easy to suppress the presence of bubbles, which are called voids, in the bundle of glass yarns during the production of a resin substrate, and thus, it is difficult to cause adverse effects on the solder heat resistance and the insulation reliability, and the like. Note that the intermolecular force of the silane coupling agent represented by the above formula (1) easily functions strongly, and thus, the impregnation of the matrix resin in the glass cloth is likely to become poor compared to a silane coupling agent other than the silane coupling agent represented by the above formula (1). Therefore, regarding the glass cloth on which the surface treatment is performed using the silane coupling agent represented by the above formula (1), the average degree of opening is preferably 35% or more, or more than 36% from the viewpoint of sufficiently obtaining the effect of improving the insulation reliability. In addition, the upper limit of the average degree of opening is 85%. If the average degree of opening is desired to be 85% or more, it is necessary to intensify the opening treatment performed on the glass cloth, and it is easy to cause a decrease in the fuzz quality of the glass cloth.
[0174] 〔Burning loss of glass cloth〕
[0175] The burning loss of the glass cloth is preferably 0.01 to 0.3% by mass, or 0.02 to 0.27% by mass, more preferably 0.03 to 0.24% by mass, further preferably 0.03 to 0.20% by mass, particularly preferably 0.03 to 0.17% by mass, from the viewpoint of easily reducing the dielectric loss tangent of the glass cloth. If the burning loss is 0.01% by mass or more, it is easy to ensure the adhesion of the resin to the glass cloth in the obtained prepreg. In this case, it is easy to ensure the heat resistance and the insulation reliability during the production of a printed wiring board. If the burning loss of the glass cloth is 0.3% by mass or less, it is easy to avoid a situation in which a surface treatment agent (or a residue thereof) that does not form a chemical bond with the surface of the glass cloth but is physically attached, a surface treatment agent (or a residue thereof) that cannot be reduced from the surface of the glass cloth by water washing, and / or a modified product thereof are present in a large amount on the surface of the glass cloth. In this case, it is easy to achieve the low dielectric loss tangent of the glass cloth.
[0176] 〔White spots of glass cloth〕
[0177] The glass cloth on which the surface treatment is performed sometimes has white spots observed in the appearance thereof. The white spots easily repel the matrix resin used during the production of a prepreg, and thus, it is possible to cause a decrease in the appearance of the obtained prepreg. In the past, the cause of the occurrence of such white spots has not been clear.
[0178] In this regard, the present inventors have ascertained that one of the above white spots exists in an aggregate of a surface treatment agent having strong hydrophobicity (for example, a silane coupling agent having strong hydrophobicity) or a modified product thereof, and the like. In particular, the present inventors have ascertained that a silane coupling agent having a value of 15.0 or less calculated from the above formula (A) has strong hydrophobicity, and thus has a tendency to easily generate aggregates, and in addition, when a solvent in the surface treatment liquid contains water, the frequency of generation of white spots in the glass cloth after surface treatment easily becomes large (for example, more than 10.0 pieces / m 2 ).
[0179] In order to suppress white spots, as described later, a method in which a surface treatment liquid is prepared by using a prescribed method, temperature management and pH management of the surface treatment liquid are performed, and the surface treatment liquid is filtered, thereby removing aggregates and the like in the surface treatment liquid, is suitable.
[0180] The frequency of generation of white spots in the glass cloth is preferably 10.0 pieces / m 2 More preferably, 7.0 pieces / m 2 Further preferably, 4.0 pieces / m 2 Still further preferably, 2.0 pieces / m 2 Still further, 0.1 pieces / m 2 In particular, 0.05 pieces / m 2 Accordingly, it is easy to achieve a prepreg having an excellent appearance.
[0181] Method for manufacturing glass cloth
[0182] The present application also provides a method for manufacturing the glass cloth of the present application. The manufacturing method of the present application includes: a weaving step of weaving a glass cloth using a glass yarn containing a plurality of glass filaments as warp yarns and weft yarns; and a surface treatment step of performing surface treatment on the glass yarn using a surface treatment liquid containing a surface treatment agent after performing an oil removal treatment on the glass yarn. The surface treatment agent is the surface treatment agent of the present application. Furthermore, the dielectric loss tangent at 10 GHz of the glass cloth after the surface treatment is preferably lower than the dielectric loss tangent at 10 GHz of the glass cloth before the surface treatment.
[0183] Here, the surface treatment step can further optionally include one or more of the following steps:
[0184] a step of heating the glass yarn, thereby reducing a fiber bundling agent adhered to the glass yarn (heating and oil removal step);
[0185] a step of washing the glass yarn with water (washing step); and / or
[0186] a step of opening the glass yarn (opening step).
[0187] As for the surface treatment step, the opening step, and the cleaning step, the glass yarn can be subjected to the steps before the process of weaving the glass yarn to obtain the glass cloth (weaving step), or the glass cloth can be subjected to the steps after the weaving step. Further, the order of the heating and deoiling step, the surface treatment step, the opening step, and the cleaning step can be changed, but the heating and deoiling step is performed before the surface treatment step. When the cleaning step is performed after the weaving step, the opening step can be performed by using a high-pressure water spray or the like in the cleaning step. Note that the composition of the glass cloth before and after the opening step is generally unchanged.
[0188] [Heating and deoiling step]
[0189] In this step, the glass yarn is heated, whereby the fiber bundling agent (sizing agent) and its residue, and their modified products or the like, which are attached to the glass yarn, are reduced, and preferably removed. By performing the heating and deoiling step, a surface treatment layer is formed on the surface of the glass yarn (glass filament) on the basis of reduction of the organic substance that increases the dielectric loss tangent, and thus, the glass cloth having excellent dielectric properties is easily produced. As a means for heating and deoiling, known means (heating means, heating medium, heating mechanism, heating device, and heating member, etc.) can be used.
[0190] As one mode of the heating and deoiling step, for example, a method in which the glass cloth is heated at a temperature of 600 to 1600°C is known.
[0191] In the heating treatment step, the glass cloth blank having a softening point of 900°C or higher is heated in a temperature range of 600 to 1600°C, whereby damage to the glass cloth is easily suppressed, and the dielectric loss tangent of the glass cloth is easily reduced. From the viewpoint of suppressing the temporal increase in the dielectric loss tangent of the glass cloth, it is preferable that the silanol group present on the surface of the glass sufficiently undergoes dehydration and condensation within a range that does not cause adverse effects in the surface treatment step as a subsequent step. By reducing the silanol group on the surface of the glass to an amount of less than or equal to a predetermined amount, the moisture in the air is suppressed from being adsorbed, and as a result, excellent dielectric properties are easily exhibited, and the temporal increase in the dielectric loss tangent is easily suppressed.
[0192] From the viewpoint of suitably obtaining excellent dielectric properties and suppressing the temporal increase in dielectric loss tangent, the heating and deoiling temperature is preferably 700 to 1500°C, more preferably 800 to 1400°C, further preferably 900 to 1300°C, and particularly preferably 1000 to 1200°C. If the heating and deoiling temperature is 600°C or higher, the sizing agent and the like adhering to the glass cloth blank is easily and effectively removed, and thus, a glass cloth having excellent dielectric properties is easily produced. If the heating and deoiling temperature is 1600°C or lower, the devitrification of the glass is easily suppressed, and as a result, the strength of the glass cloth is easily prevented from decreasing.
[0193] The heating time is preferably 1 hour or less, or 30 minutes or less, more preferably 15 minutes or less, and further preferably 5 minutes or less. By heating the glass cloth at a high temperature for a sufficient time, the dehydration condensation reaction of the silanol group on the surface of the glass is easily induced. From the viewpoint of effectively removing the sizing agent and the like, the heating time can be, for example, 1 second or more, 5 seconds or more, 10 seconds or more, or 15 seconds or more.
[0194] When the heating and deoiling of the glass cloth is performed in a closed system, from the viewpoint of suitable heating based on the heating means, the glass cloth is preferably disposed in a heating furnace. In addition, from the viewpoint of efficiency of the storage space and the heating range, the glass cloth is preferably heated while being stored in a state of a roll of cloth. Furthermore, from the viewpoint of improving the removal efficiency of the organic substance and the viewpoint of shortening the removal time of the organic substance, the glass cloth is preferably heated while being transported in the heating furnace. The transportation of the glass cloth can be performed by, for example, a combination of an unwinding mechanism and a winding mechanism.
[0195] When the heating and deoiling of the glass cloth is performed in an open system, from the viewpoint of securing the heated area, the glass cloth is preferably heated while being transported. The transportation of the glass cloth can be performed by, for example, a combination of an unwinding mechanism and a winding mechanism.
[0196] The mode of the heating and deoiling step is not limited to the above-described mode.
[0197] As another mode of the heating and deoiling step, for example, the following methods are also known:
[0198] a method in which heating is performed in a vacuum or in a gas having a dew point of 15°C or lower, under conditions in which the amount of heating expressed by the product of the heating temperature (°C) by the heating time (h) is 450 (°C·h) or more (wherein the maximum heating temperature is 100 to 600°C), and the like.
[0199] (Heating Means)
[0200] As the heating means, for example, a heating furnace, an electric heater, a burner, and the like can be considered, and a gas-type single radiant tube burner or an electric heater is preferable. A plurality of different heating means can be combined.
[0201] From the viewpoint of efficiently removing organic substances adhering to the surface of the glass cloth, a continuous method in which the glass cloth is continuously fed into a heating furnace while being heated is more preferable than an intermittent method in which the glass cloth wound around a winding core is heated at a prescribed atmosphere temperature. A method in which the glass cloth cleaning is continuously performed using cleaning water having a low content of metal ions such as reverse osmosis (RO) water or ion-exchange water is more preferable.
[0202] When the sodium ions adhering to the glass cloth exceed a prescribed amount, if the glass cloth is heated to remove oil at 700°C or higher, the tensile strength of the glass cloth can sometimes decrease due to devitrification of the quartz glass. In contrast, in order to suppress the devitrification, if the glass cloth is cleaned with water having a sodium ion content of 20 ppm or less before the heating to remove oil, the amount of sodium ions in the glass surface is easily reduced, and in this case, even if the heating to remove oil is performed at 700°C or higher, the devitrification of the quartz glass is easily suppressed. By maintaining the strength of the glass cloth after the heating to remove oil, the glass cloth is easily prevented from being wrinkled and / or damaged, and the like, in the surface treatment process.
[0203] From the viewpoint of suitably obtaining excellent dielectric properties and suppressing the temporal increase in the dielectric loss tangent, the sodium ion content in the water used for the cleaning can be 18 ppm or less, 15 ppm or less, 12 ppm or less, 10 ppm or less, or 7 ppm or less. The sodium ion content is preferably 0 ppm, but can exceed 0.
[0204] The method of cleaning the glass cloth under the condition that the sodium ion content is 20 ppm or less can be a known cleaning method as long as it can remove the sodium ions from the surface of the glass. For example, a method using ultrasonic waves (for example, a method using an ultrasonic vibrator), a method based on spraying (for example, a method based on high-pressure spraying), a water vapor spraying method, and the like can be considered. From the viewpoint of being able to be processed at a low cost, a method in which the glass cloth is immersed in a water tank containing cleaning water (water having a sodium ion content of 20 ppm or less), the excess cleaning water is removed using a press roll or the like, and then the glass cloth is dried is preferable. In this case, the immersion time can be, for example, 2 seconds or more, 5 seconds or more, 10 seconds or more, 15 seconds or more, or 120 seconds or less, 90 seconds or less, 60 seconds or less, or 45 seconds or less.
[0205] The method of producing water having a sodium ion content of 20 ppm or less can be a known production method. For example, a method using a RO membrane for filtration, a method using ion-exchange resin for deionization, and the like can be considered. The "water having a sodium ion content of 20 ppm or less" can contain other liquid components (liquids other than water, and the like) within a range that does not impair the effects of the present application.
[0206] From the perspective of promoting the dehydration condensation reaction of silanol groups on the glass surface, it is preferable to keep the surrounding environment as moisture-free as possible during the period from the start of thermal deoiling until the temperature of the glass cloth surface drops to 100°C or below. In other words, it is preferable to reduce the surrounding moisture during thermal deoiling. Known methods for reducing the surrounding moisture during thermal deoiling include, for example, introducing dry air into the heating furnace, creating a vacuum in the furnace, and introducing an inert gas such as nitrogen into the furnace. When thermal deoiling is performed while the glass cloth is being transported, introducing an inert gas such as nitrogen into the furnace is preferred.
[0207] 〔Surface treatment process〕
[0208] In this process, the glass yarn is surface-treated using a surface treatment solution containing a prescribed surface treatment agent, particularly a prescribed silane coupling agent (in one embodiment, a silane coupling agent advantageous from the perspective of reducing the dielectric loss tangent of the glass cloth). The silane coupling agent used in the method of the present application is more hydrophobic than conventional silane coupling agents. As described above, the present inventors have clearly found that when the solvent in the surface treatment solution contains water, there is a tendency for aggregates of the surface treatment agent to form. In addition, when the solvent in the surface treatment solution contains water, the frequency of white spots on the surface-treated glass cloth tends to increase.
[0209] Examples of methods for treating glass yarn with a surface treatment liquid (for example, a method of applying a surface treatment liquid to glass yarn) include:
[0210] (1) A method in which the glass cloth is transported while being immersed in the surface treatment liquid accumulated in the bath (hereinafter referred to as the "immersion method");
[0211] (2) Methods in which the surface treatment liquid is directly applied to the glass cloth using a roll coater, die coater, or gravure coater.
[0212] When the dipping method is used, the immersion time of the glass cloth in the surface treatment liquid is preferably selected to be 0.5 seconds to 1 minute.
[0213] (Surface treatment liquid)
[0214] The surface treatment liquid of the present application is a surface treatment liquid containing a surface treatment agent, which can be used for surface treatment of glass cloth. The surface treatment agent has a molecular structure with a value of 15.0 or less as determined by the following formula (A).
[0215] 1.10×MaxEStateIndex+14.6×MaxPartialCharge-0.0917×SPS+2.47×HallKierAlpha…(A)
[0216] Further, in the surface treatment agent contained in the above-mentioned surface treatment liquid, the silane coupling agent represented by the above-mentioned formula (1) is preferably contained. In the surface treatment step, the glass yarn is preferably treated using a surface treatment liquid containing a surface treatment agent having a molecular weight of 200 or more. Further, the details of the surface treatment agent are as described in the item of "Glass Cloth" above.
[0217] The present inventors have found that, for a prescribed surface treatment liquid, white spots of the glass cloth can be suppressed by, for example, any one or more of the following (A) to (C).
[0218] (A) The surface treatment liquid is prepared by adding an acidic aqueous solution to a hydrolyzed solution of the surface treatment agent;
[0219] (B) The temperature and / or the pH of the surface treatment liquid are controlled; and / or
[0220] (C) The surface treatment liquid is filtered.
[0221] (A) Preparation of the surface treatment liquid
[0222] A general silane coupling agent has excellent compatibility with water and dispersibility in water, and thus is prepared by adding a hydrolyzed solution (also referred to as a "pre-solution" in the present application) of the silane coupling agent to weakly acidic water having a pH of about 3 to 5 while stirring. In the method of the present application, on the other hand, the surface treatment liquid is preferably prepared by adding an acidic aqueous solution to the silane coupling agent. More preferably, a pre-solution containing the surface treatment agent is prepared, and an acidic aqueous solution is added to the resulting pre-solution. More specifically, a dilute solution obtained by diluting the surface treatment agent with a small amount of methanol is added with a surfactant and a small amount of a solvent (for example, an aqueous acetic acid solution having a concentration of 60%) for hydrolysis of the silane coupling agent, whereby a hydrolyzed solution (pre-solution) of the surface treatment agent can be obtained. Note that, as for the solvent in the pre-solution, it is preferable that the solvent be added in an amount adjusted in accordance with the amount of hydrolysis in order to hydrolyze the alkylol group of the silane coupling agent. Further, by adding an acidic aqueous solution (also referred to as a "mother solution" in the present application) to the pre-solution while stirring, the surface treatment agent can be uniformly dispersed in the aqueous solution. In this case, the formation of aggregates in the surface treatment liquid is easily suppressed. The acidic aqueous solution as the mother solution is preferably a weakly acidic aqueous solution, for example, a weakly acidic aqueous solution having a pH adjusted to 2.5 or more and 5.5 or less, 3.0 or more and 5.0 or less, 3.0 or more and 4.5 or less, or 3.0 or more and 4.0 or less. As the weak acid, for example, a carboxylic acid having the general formula RCOOH, R being an alkyl group having 1 to 10 carbon atoms, optionally substituted or unsubstituted, optionally linear or branched, can be used. As the weak acid, formic acid, acetic acid, propionic acid, and the like can be preferably used.
[0223] As the "small amount of solvent for hydrolyzing the silane coupling agent", an acidic aqueous solution as the above mother liquid can be used. In addition, as the mother liquid, a solvent for hydrolyzing the silane coupling agent (for example, an aqueous acetic acid solution having a concentration of 60%) can be used.
[0224] (concentration of the silane coupling agent)
[0225] In the present application, the concentration of the silane coupling agent in the surface treatment agent is preferably in the range of 0.20 to 1.2% by mass. More preferably, it is in the range of 0.25 to 1.1% by mass, further preferably in the range of 0.30 to 1.0% by mass, still further preferably in the range of 0.33 to 0.9% by mass, and particularly preferably in the range of 0.35 to 0.7% by mass. If the concentration of the silane coupling agent is 1.2% by mass or less, the amount of the silane coupling agent adhered to the surface of the glass cloth decreases, and the dielectric loss tangent of the glass cloth decreases. If the concentration of the silane coupling agent is 0.2% by mass or more, the amount of the silane coupling agent adhered to the surface of the glass cloth increases, and the adhesion to the matrix resin improves, and thus, the heat resistance and the like of the laminated board are improved.
[0226] As the surfactant, any one of a nonionic surfactant, an anionic surfactant, a cationic surfactant, and an amphoteric surfactant can be used, and the kind and the amount thereof can be appropriately changed according to the kind and the amount of the surface treatment agent, and the like. Different kinds of surfactants can be used in combination.
[0227] As the nonionic surfactant, glycerin fatty acid ester, sorbitan fatty acid ester, sucrose fatty acid ester, polyoxyethylene alkyl ether, polyoxyethylene alkyl phenyl ether, polyoxyethylene polyoxypropylene glycol, fatty acid polyethylene glycol, polyoxyethylene sorbitan fatty acid ester, fatty acid alkanolamide, and the like can be exemplified.
[0228] As the anionic surfactant, fatty acid monocarboxylate, polyoxyethylene alkyl ether carboxylate, N-acyl sarcosinate, N-acyl glutamate, dialkyl sulfosuccinate, alkane sulfonate, alpha olefin sulfonate, linear alkyl benzene sulfonate, alkyl benzene sulfonate, naphthalene sulfonate-formaldehyde condensate, alkyl naphthalene sulfonate, N-methyl-N-acyl taurate, alkyl sulfate, polyoxyethylene alkyl ether sulfate, oil fatty acid ester sulfate, alkyl phosphate, polyoxyethylene alkyl ether phosphate, polyoxyethylene alkyl phenyl ether phosphate, and the like can be exemplified.
[0229] As the cationic surfactant, monoalkyl amine salt, dialkyl amine salt, trialkyl amine salt, alkyl trimethyl ammonium chloride, alkyl benzalkonium chloride, and the like can be exemplified.
[0230] As the amphoteric surfactant, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolium betaine, alkyl betaine, fatty acid amide propyl betaine, alkyl diethylene triamino acetic acid, alkyl amine oxide, and the like can be exemplified.
[0231] (concentration of surfactant)
[0232] In the present application, the concentration of the surfactant in the surface treatment liquid is preferably in the range of 0.5 to 5.0 mass% relative to the above-mentioned silane coupling agent. More preferably, it is in the range of 1.0 to 4.5 mass%, further preferably in the range of 1.5 to 4.0 mass%, still further preferably in the range of 1.8 to 3.7 mass%, and particularly preferably in the range of 2.0 to 3.5 mass%. If the concentration of the surfactant is 5.0 mass% or less relative to the above-mentioned silane coupling agent, the amount of the surfactant adhered to the surface of the glass cloth is reduced, and the CAF resistance of the laminate is improved. If the concentration of the surfactant is 0.5 mass% or more relative to the above-mentioned silane coupling agent, the water dispersibility of the silane coupling agent is improved, and thus, it is easy to control the frequency of occurrence of white spots to 10 / m 2 .
[0233] (B) Temperature control and / or pH control of the surface treatment liquid
[0234] From the viewpoint of inhibiting aggregates in the surface treatment liquid, it is preferable to have a step of controlling the temperature of the surface treatment liquid during the surface treatment. As the temperature range, it is preferable to control it at 10 to 30°C, more preferably at 13 to 27°C, further preferably at 15 to 25°C, and particularly preferably at 17 to 23°C.
[0235] In addition, during the surface treatment, the pH of the surface treatment liquid sometimes fluctuates due to impurities such as alkali metals contained in a small amount in the glass cloth. From the viewpoint of inhibiting aggregates in the surface treatment liquid, it is preferable to have a step of controlling the pH of the surface treatment liquid. During the surface treatment process, the pH of the surface treatment liquid is preferably controlled at 2.5 to 5.5, more preferably at 2.8 to 5.2, further preferably at 3.0 to 5.0, 3.0 to 4.5, or 3.0 to 4.0. As a method of controlling the pH to a prescribed range, a method of bubbling carbon dioxide into the surface treatment liquid, and the like can be exemplified.
[0236] As for the temperature control of the surface treatment liquid and the pH control of the surface treatment liquid, either one of the controls can be performed, or both of the controls can be performed. From the viewpoint of suitably inhibiting aggregates in the surface treatment liquid, it is preferable to perform both of the temperature control of the surface treatment liquid and the pH control of the surface treatment liquid.
[0237] Here, the "temperature control of the surface treatment liquid" refers to any one of the operation of increasing and / or decreasing the temperature of the surface treatment liquid, the operation of maintaining the temperature of the surface treatment liquid to a prescribed value, and the operation of detecting the temperature of the surface treatment liquid in order to determine whether the temperature falls within a prescribed range. In addition, the "pH control of the surface treatment liquid" refers to any one of the operation of increasing and / or decreasing the pH of the surface treatment liquid, the operation of maintaining the pH of the surface treatment liquid to a prescribed value, and the operation of detecting the pH of the surface treatment liquid in order to determine whether the pH falls within a prescribed range.
[0238] (C) Filtration of the surface treatment liquid
[0239] From the viewpoint of reliably capturing the aggregates in the surface treatment liquid, it is preferable to perform filtration of the surface treatment liquid during the surface treatment. At this time, it is preferable to capture the aggregates that can be generated in the surface treatment liquid by filtration while circulating the surface treatment liquid.
[0240] From the viewpoint of improving the capturing efficiency of the aggregates, it is preferable to perform the filtration in multiple stages. For example, it is preferable to perform two-stage filtration of performing once removal of the aggregates using a filter having a relatively coarse mesh, and then performing filtration of the surface treatment liquid using a filter having a finer mesh than the once filter. According to such multiple-stage filtration, it is easy to prevent clogging of the mesh of the filter, and as a result, it is easy to avoid interruption of the production process of the glass cloth.
[0241] (Drying step)
[0242] The surface treatment step can further include a step of drying the solvent contained in the surface treatment liquid after the glass yarn is coated with the surface treatment liquid (drying step). According to the drying step, it is easy to fix the surface treatment agent to the surface of the glass yarn (the surface of the glass filament), and in particular, it is easy to fix the surface treatment agent to the surface of the 1-denier glass yarn (the surface of the 1-denier glass filament). As a method of drying the solvent, known methods such as a method of drying by heating, specifically, a method of drying by heating with hot air and electromagnetic waves, and the like can be exemplified.
[0243] From the viewpoint of sufficiently performing the reaction of the surface treatment agent with the glass, the drying temperature is preferably 80°C or higher, and more preferably 90°C or higher. In addition, from the viewpoint of preventing deterioration of the organic functional group possessed by the surface treatment agent, the drying temperature is preferably 300°C or lower, and more preferably 180°C or lower.
[0244] 〔Opening step〕
[0245] The production method of the present application preferably has an opening process after the surface treatment process. As the opening method in the opening process, for example, a method of opening the glass cloth by using a spray of water (high-pressure water opening), a vibration cleaner, ultrasonic water, a mangle, and the like can be exemplified. In this opening process, the yarn width of the glass yarn is easily expanded by reducing the tension applied to the glass cloth, and, in addition, the surface treatment agent that is not chemically bonded to the surface of the glass is easily removed to some extent. In order to suppress the reduction in the tensile strength of the glass cloth caused by the opening process, countermeasures such as the low-frictionization of the contact member at the time of weaving the glass yarn, the optimization and high adhesion of the binder, and the like are preferably implemented.
[0246] [Cleaning Process]
[0247] As the cleaning process, a method capable of reducing the residue and modified product and the like of the surface treatment agent that does not form a chemical bond with the surface of the glass filament can be exemplified, for example, a method of cleaning the glass yarn by using an organic solvent and the like. By performing the cleaning process, even if a glass raw material having a high content of silicon (Si), such as quartz glass, is used, it is easy to adjust the difference between the dielectric loss tangent of the obtained glass cloth and the bulk dielectric loss tangent to a prescribed range.
[0248] As the cleaning process, in order to achieve the reduction of the above-described residue and the like that is difficult to reduce with water, it is preferable to perform the cleaning by using an organic solvent having a high hydrophobicity, and, in addition, it is preferable to perform the cleaning by using an organic solvent having a high affinity with the silane coupling agent residue and the like having a hydroxyl group. As the cleaning method, known methods such as an immersion method, a spray, and the like can be exemplified, and the cleaning can be performed while heating or cooling as needed. In order not to cause the reattachment of the glass cloth attachment that has been dissolved, it is preferable to reduce the excess solvent before drying by using a press roll and the like with respect to the glass cloth after the cleaning. As the suitable organic solvent, for example, an organic solvent having a high hydrophobicity, saturated chain aliphatic hydrocarbons such as n-pentane, isopentane, n-hexane, isohexane, n-heptane, isohexane, n-octane, isooctane, 2,2,4-trimethylpentane (isooctane), n-nonane, isononane, n-decane, isodecane, 2,2,4,6,6-pentamethylheptane (isododecane), and the like; saturated cyclic aliphatic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, ethylcyclohexane, and the like; aromatic hydrocarbons such as benzene, toluene, xylene, ethylbenzene, diethylbenzene, trimethylbenzene, triethylbenzene, and the like; halogen-containing solvents such as chloroform, dichloromethane, dichloroethane, and the like, and the like can be exemplified.
[0249] As the organic solvent having a high affinity with the modified product of the surface treatment agent (for example, a silane coupling agent), alcohols such as methanol, ethanol, butanol, and the like; ketones such as acetone, methyl ethyl ketone, and the like; ethers such as methyl ethyl ether, diethyl ether, and the like; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and the like; dimethyl sulfoxide, and the like can be exemplified.
[0250] Among the above, from the viewpoint of easily adjusting the difference between the tangent of the dielectric loss angle of the obtained glass cloth and the tangent of the bulk dielectric loss angle to a prescribed range, an aromatic hydrocarbon, an alcohol, or a ketone is preferred, and methanol is more preferred.
[0251] In the production method of the present application, in order to reduce the organic solvent after washing, it is preferred to have a step of drying the glass cloth after washing (post-washing drying step), and from the viewpoint of easily reducing the organic solvent by drying, the organic solvent used in the washing is preferably one having a boiling point of 120°C or lower. In the drying of the organic solvent, known methods such as heat drying, air blowing drying, etc. can be used.
[0252] In the post-washing drying step, when heat drying is performed in order to reduce the organic solvent, from the viewpoint of safety, hot air drying using low-pressure steam or hot medium oil as a heat source is preferred. The drying temperature is preferably the boiling point of the washing solvent or higher, and from the viewpoint of suppressing the deterioration of the silane coupling agent, it is preferably 180°C or lower.
[0253] [Optional Step]
[0254] In the production method of the present application, other steps can be optionally included in addition to the above steps. As the other steps, a step of processing the glass cloth into a slit shape (slit processing step) can be cited, for example.
[0255] [Inspection Step or Measurement Step]
[0256] In addition, as the other steps, a step of inspecting the white spots of the glass cloth can be cited. The production method of the present application easily achieves the glass cloth of the present application by including this step.
[0257] [Prepreg]
[0258] The prepreg of the present application contains a glass cloth, a matrix resin, and an inorganic filler. In the prepreg of the present application, the above glass cloth of the present application can be used as the glass cloth. Thereby, a prepreg having various excellent properties (for example, a prepreg having few voids) is provided.
[0259] As the matrix resin, both thermosetting resins and thermoplastic resins can be used. Thermosetting resins and thermoplastic resins can also be used in combination.
[0260] As the thermosetting resin, for example, the following can be cited:
[0261] a) an epoxy resin obtained by reacting a compound having an epoxy group with a compound having at least one of an amino group, a phenolic group, an acid anhydride group, a hydrazide group, an isocyanate group, a cyanate group, a hydroxyl group, and the like, which reacts with the epoxy group, under catalyst-free conditions, or by adding a catalyst having a reaction catalytic ability such as an imidazole compound, a tertiary amine compound, a urea compound, a phosphorus compound, and the like, and reacting, and curing;
[0262] b) a free radical polymerization type curing resin obtained by curing a compound having at least one group selected from the group consisting of an allyl group, a methallyl group, and an acryloyl group, using a thermal decomposition type catalyst or a photodecomposition type catalyst as a reaction initiator;
[0263] c) a maleimide triazine resin obtained by reacting a compound having a cyanate ester group with a compound having a maleimide group and curing the same;
[0264] d) a thermosetting polyimide resin obtained by reacting a maleimide compound with an amine compound and curing the same;
[0265] e) a benzoxazine resin obtained by crosslinking and curing a compound having a benzoxazine ring by polymerization through heating, and the like.
[0266] As the thermoplastic resin, for example, polyphenylene ether, modified polyphenylene ether, polyphenylene sulfide, polysulfone, polyethersulfone, polyarylate, aromatic polyamide, polyether ether ketone, thermoplastic polyimide, insoluble polyimide, polyamide-imide, LCP, polyester, fluororesin, and the like can be exemplified.
[0267] The prepreg can contain an inorganic filler. As the inorganic filler, for example, aluminum hydroxide, zirconium oxide, calcium carbonate, aluminum oxide, mica, aluminum carbonate, magnesium silicate, aluminum silicate, silicon dioxide, talc, glass short fibers, aluminum borate, and silicon carbide, and the like can be exemplified. The inorganic filler can be used in combination with the thermosetting resin.
[0268] Printed circuit board
[0269] The printed circuit board of the present application contains the prepreg described above. In particular, the printed circuit board of the present application can be formed using the prepreg described above of the present application as the prepreg. Thereby, a printed circuit board excellent in various properties (for example, a printed circuit board excellent in insulation reliability) can be provided.
[0270] Integrated circuit and electronic device
[0271] The integrated circuit of the present application contains the printed circuit board described above of the present application. In addition, the electronic device of the present application contains the printed circuit board described above of the present application. Thereby, an integrated circuit and an electronic device excellent in various properties can be provided. As the electronic device, an information terminal such as a smartphone can be exemplified, and the integrated circuit can be used for high performance of the electronic device and high speed communication represented by 5G communication.
[0272] Examples
[0273] Hereinafter, examples and comparative examples are exemplified to explain the present application. The present application is not limited only to the following examples. With respect to the examples and comparative examples, various production, measurement, evaluation, and the like are performed by the following methods.
[0274] Measurement and evaluation method
[0275] 〔Calculation of formula A〕
[0276] The formula (A) of the silane coupling agent is calculated by the following described operation.
[0277] (1) MaxEStateIndex, MaxPartialCharge, SPS, HallKierAlpha included in formula (A) are calculated by using open source software called RDKit. Note that the version of RDKit used is 2023.09.4.
[0278] (2) The silane coupling agent shown in the following structure is converted to a silanol structure by converting (-Y) as an alkoxy or halogen group to a hydroxyl group (-OH). 4-n -Si(OH) n .
[0279] Silane coupling agent: X 4-n -Si-Y n
[0280] X is each independently an organic functional group, n is an integer of 1 or more and 3 or less, and Y is each independently an alkoxy group or a halogen group.
[0281] (3) The silane coupling agent converted to a silanol structure produced by operation (2) is converted to a chemical structure in SMILES notation (simplified molecular input line entry system) obtained by stringing ASCII symbols of alphabetic characters and symbols.
[0282] (4) With respect to the structure in SMILES notation produced by operation (3), a MOL object is produced using the MolFromSmiles method of the rdkit.Chem.rdmolfiles module in RDKit.
[0283] (5) With respect to the MOL object produced by operation (4), calculation is performed using the MaxEStateIndex method of the rdkit.Chem.EState.EState module in RDKit with respect to the descriptor MaxEStateIndex.
[0284] (6) With respect to the descriptor MaxPartialCharge, for the MOL object made by operation (4), the MaxPartialCharge method of the rdkit.Chem.Descriptors module in RDKit was used to calculate.
[0285] (7) With respect to the descriptor SPS, for the MOL object made by operation (4), the SPS method of the rdkit.Chem.SpacialScore module in RDKit was used to calculate.
[0286] (8) With respect to the descriptor HallKierAlpha, for the MOL object made by operation (4), the HallKierAlpha method of the rdkit.Chem.GraphDescriptors module in RDKit was used to calculate.
[0287] (MaxEStateIndex, MaxPartialCharge, SPS, HallKierAlpha, linear sum of values)
[0288] Using the values of MaxEStateIndex, MaxPartialCharge, SPS, and HallKierAlpha obtained by the above operations, the linear sum of the values of these descriptors was calculated according to the following formula.
[0289] 1.10 x MaxEStateIndex + 14.6 x MaxPartialCharge - 0.0917 x SPS + 2.47 x HallKierAlpha
[0290] 〔Thickness〕
[0291] With respect to the thickness of the glass cloth, according to 7.10 of JIS R 3420, using a micrometer, the mandrel was lightly rotated to make it lightly contact the measuring surface in parallel, and the scale after the ratchet emitted 3 sounds was read. Note that JIS R 3420 prescribes general test methods for glass long fibers and products such as glass cloth obtained using glass long fibers.
[0292] 〔Weight per unit area〕
[0293] The glass cloth was cut to a prescribed size to obtain a sample. The weight per unit area was calculated by dividing the mass of the sample by the area of the sample. Here, the glass cloth was cut to a size of 10 cm x 10 cm to obtain a sample, and the mass thereof was measured to thereby calculate the weight per unit area (g / m 2 ).
[0294] 〔Conversion thickness〕
[0295] The glass cloth is a discontinuous planar body formed of air and glass, and therefore, the conversion thickness required when measured by the resonance method is calculated by dividing the weight per unit area of each glass cloth by the density of the glass. The calculation formula is shown in the following formula:
[0296] Conversion thickness (μm) = Weight per unit area (g / m 2 ) ÷ Density of glass (g / cm 3 )
[0297] 〔Dielectric loss tangent〕
[0298] The dielectric loss tangent of each glass cloth was measured in accordance with IEC 62562. Specifically, a glass cloth sample sampled in a size required for measurement with each split post resonator was stored in a constant temperature and humidity oven at 23°C, 50% RH for 8 hours, and was subjected to humidity conditioning. Thereafter, using a split post resonator (manufactured by EM LABO) and an impedance analyzer (manufactured by Agilent Technologies), the dielectric properties at 10 GHz were measured. The measurement was performed 5 times for each sample, and the average value was obtained. In addition, as the thickness of each sample, the conversion thickness described above was used, and the dielectric loss tangent of the glass cloth was obtained. In addition, as for the bulk dielectric loss tangent of the glass, a glass plate having the same composition as the glass cloth was prepared, and the bulk dielectric loss tangent was obtained using a split post in accordance with the thickness of the glass plate. Note that the measurement method of the dielectric properties of a fine ceramic material for dielectric substrates for microwave circuits in the microwave band is prescribed in IEC 62562.
[0299] 〔Increase in dielectric loss tangent over time〕
[0300] The dielectric loss tangent of the glass cloth can increase due to moisture present in the storage environment. Using a constant temperature and humidity machine, the glass cloth was stored in an environment of high temperature and high humidity (40°C, 90% RH) for 1 week, and the increase in the dielectric loss tangent before and after storage (dielectric loss tangent after storage - dielectric loss tangent before storage) was obtained.
[0301] (Conditions)
[0302] Storage conditions: 40°C x 90% RH
[0303] Storage period: 1 week
[0304] Dielectric loss tangent: the measurement method described in the above 〔Dielectric loss tangent〕
[0305] 〔Ignition loss value〕
[0306] The loss on ignition of the glass cloth was found in accordance with JIS R3420. Specifically, the glass cloth was dried at a temperature of 110°C ± 5°C for 60 minutes. Next, it was transferred to a desiccator, and after natural cooling at room temperature for 20 minutes, the mass of the test piece was measured to the unit of 0.1 mg (Amg). The dried test piece was subjected to heat treatment at a temperature of 625°C ± 20°C for 20 minutes. Next, it was transferred to a desiccator, and after natural cooling for 20 minutes, the mass of the test piece was measured to the unit of 0.1 mg (B mg). The loss on ignition was found using the following formula, and rounded off to the fourth decimal place, expressed to the third decimal place.
[0307] Loss on ignition (%) = [{A(mg) - B(mg)} / A(mg)] x 100
[0308] (Average opening degree)
[0309] The opening degree of the warp yarn of the glass cloth was calculated using the following formula:
[0310] Opening degree of warp yarn (%) = [warp yarn width (μm) / {number of filaments of warp yarn x filament diameter of warp yarn (μm)}] x 100
[0311] In addition, the opening degree of the weft yarn of the glass cloth was calculated using the following formula:
[0312] Opening degree of weft yarn (%) = [weft yarn width (μm) / {number of filaments of weft yarn x filament diameter of weft yarn (μm)}] x 100
[0313] Using the calculated opening degree of the warp yarn (%) and the opening degree of the weft yarn (%), the average opening degree was calculated using the following formula:
[0314] Average opening degree (%) = {opening degree of warp yarn (%) + opening degree of weft yarn (%)} / 2
[0315] (Number of filaments of warp yarn and weft yarn)
[0316] In calculating the average opening degree, the number of filaments of the warp yarn and the weft yarn was found by observation of the cross-sectional image of the glass yarn. Specifically, the cross-sectional image of the glass yarn as the warp yarn (or the weft yarn) was obtained, and the number of filaments of the warp yarn (or the weft yarn) was measured in the cross-sectional image. Similarly, the image acquisition of the glass yarn and the measurement of the number of filaments were repeated, and the average of the 5 measured values obtained was taken as the number of filaments of the warp yarn (or the weft yarn).
[0317] (Warp yarn width and weft yarn width)
[0318] In calculating the average opening degree, the warp width and the weft width are calculated by the following method. First, five test pieces of glass cloth having a size of 70 mm in the warp direction and 70 mm in the weft direction are cut out from the glass cloth. For the cut-out test pieces, a microscope is used to observe from the perpendicular direction at a magnification of 100 times. For each of the test pieces, the yarn widths of 250 warps (or wefts) are randomly measured, and the average of the measured yarn widths of the 250 warps (or wefts) is calculated. The calculated average is taken as the warp width (or weft width).
[0319] Example of Production of Glass Cloth
[0320] [Glass Cloth P]
[0321] Warp yarns and weft yarns composed of glass yarns having a Si02content of more than 99.9 mass% were used. Specifically, as the warp yarns and the weft yarns, glass yarns each having an average filament diameter of 5.0 μm, a number of filaments of 100, and a twist number of 1.0 Z were used. Further, using an air jet loom, a glass cloth 2000 m having a plain weave structure, a cloth width of 1300 mm, and a weaving density of 66 warps / 25 mm and 68 wefts / 25 mm was woven. Note that the glass constituting the used glass yarns had a bulk dielectric loss tangent of 0.00020 at 10 GHz.
[0322] [Glass Cloth Q]
[0323] Warp yarns and weft yarns composed of glass yarns having a Si02content of more than 99.9 mass% were used. Specifically, as the warp yarns and the weft yarns, glass yarns each having an average filament diameter of 5.0 μm, a number of filaments of 200, and a twist number of 1.0 Z were used. Further, using an air jet loom, a glass cloth 2000 m having a plain weave structure, a cloth width of 1300 mm, and a weaving density of 54 warps / 25 mm and 54 wefts / 25 mm was woven. Note that the glass constituting the used glass yarns had a bulk dielectric loss tangent of 0.00020 at 10 GHz.
[0324] [Glass Cloth R]
[0325] Warp yarns and weft yarns composed of glass yarns having a Si02content of more than 99.9 mass% were used. Specifically, as the warp yarns and the weft yarns, glass yarns each having an average filament diameter of 4.0 μm, a number of filaments of 50, and a twist number of 1.0 Z were used. Further, using an air jet loom, a glass cloth 2000 m having a plain weave structure, a cloth width of 1300 mm, and a weaving density of 95 warps / 25 mm and 95 wefts / 25 mm was woven. Note that the glass constituting the used glass yarns had a bulk dielectric loss tangent of 0.00020 at 10 GHz.
[0326] Preparation Example of Surface Treatment Liquid
[0327] [Preparation Method I: Addition of mother liquor to pre-solution of silane coupling agent]
[0328] The surface treatment liquid is prepared by the following methods 1) to 6).
[0329] 1) The silane coupling agent is weighed.
[0330] 2) A silane coupling agent solution is prepared by mixing methanol in an amount equivalent to the amount weighed in 1) above with the silane coupling agent weighed in 1) above.
[0331] 3) The silane coupling agent solution is mixed with polyoxyethylene alkyl ether in an amount of 0.8 mass% based on the mass of the silane coupling agent weighed in 1) above, and stirred for 1 minute.
[0332] 4) To the silane coupling agent solution stirred in 3) above, an aqueous acetic acid solution having a concentration of 60 mass% is added in an amount of 20 mass% based on the mass of the silane coupling agent weighed in 1) above. Thus, a pre-solution of the hydrolyzed silane coupling agent (hydrolysis solution) is obtained.
[0333] 5) A mother liquor of aqueous acetic acid solution (pH = 3 to 4) is prepared. In addition, the pre-solution of the silane coupling agent obtained in 4) above is stirred at room temperature of 20 to 25°C for 15 minutes. At this time, the mother liquor is added to the pre-solution of the silane coupling agent being stirred, whereby the silane coupling agent is dispersed. The amount and rate of addition of the mother liquor are set so that the addition of the entire mother liquor is completed within 10 minutes.
[0334] 6) After 5) above, the silane coupling agent solution is stirred at room temperature of 20 to 25°C for 2 hours, whereby the surface treatment liquid is obtained.
[0335] [Preparation Method II: Addition of pre-solution of silane coupling agent to mother liquor]
[0336] The surface treatment liquid is prepared by the following methods 1) to 6).
[0337] 1) The silane coupling agent is weighed.
[0338] 2) A silane coupling agent solution is prepared by mixing methanol in an amount equivalent to the amount weighed in 1) above with the silane coupling agent weighed in 1) above.
[0339] 3) The silane coupling agent solution is mixed with polyoxyethylene alkyl ether in an amount of 0.8 mass% based on the mass of the silane coupling agent weighed in 1) above, and stirred for 1 minute.
[0340] 4) To the silane coupling agent solution subjected to stirring in the above 3), an aqueous acetic acid solution having a concentration of 60 mass% was added in a manner so as to become 20 mass% based on the mass of the silane coupling agent weighed out in the above 1). Thus, a pre-solution (hydrolysis solution) containing a hydrolyzed silane coupling agent was obtained.
[0341] 5) A mother liquor of an aqueous acetic acid solution (pH = 3 to 4) was prepared. In addition, the silane coupling agent pre-solution obtained in the above 4) was stirred at room temperature of 20 to 25°C for 15 minutes. At this time, the stirred silane coupling agent pre-solution was added to the above mother liquor, whereby the silane coupling agent was dispersed. The addition amount and the addition rate of the pre-solution were set to a condition in which the entire pre-solution was added within 10 minutes.
[0342] 6) After the above 5), the silane coupling agent solution was stirred at room temperature of 20 to 25°C for 2 hours, whereby a surface treatment liquid was obtained.
[0343] "Examples and Comparative Examples"
[0344] [Example of Production of Glass Cloth]
[0345] (Example 1)
[0346] The glass cloth P was washed with ion-exchange water, and then dried. Thus, alkali metal ions and the like adhering to the surface of the glass cloth were removed. Thereafter, the glass cloth was heated and deoiled in a furnace in which the set temperature was adjusted to 700°C while being transported for 30 seconds (heating and deoiling step).
[0347] As the silane coupling agent, 3,6-divinyl-l-(trimethoxysilyl)naphthalene (CAS NO: 2230040-75-0, molecular weight = 300.42, silane coupling agent A) represented by the following formula was used, and a surface treatment liquid was prepared using the above Preparation Method I in a manner so that the silane coupling agent concentration in the surface treatment liquid became 0.35 mass%.
[0348]
[0349] The glass cloth after the heating and deoiling was immersed in the obtained surface treatment liquid. Furthermore, the excess surface treatment liquid was squeezed out with a rubber roll made of NBR at a pressure of 0.3 MPa. Thereafter, the glass cloth was heated and dried at 130°C for 1 minute, whereby the silane coupling agent was fixed to the surface of the glass cloth.
[0350] Here, in the present embodiment, temperature management (e.g., cooling) is performed in such a manner that the temperature of the surface treatment liquid becomes in the range of 17 to 23°C during the surface treatment of the glass cloth. In addition, carbon dioxide is blown into the surface treatment liquid in such a manner that the pH of the surface treatment liquid becomes in the range of 3.0 to 4.0 during the surface treatment of the glass cloth.
[0351] In addition, in the present embodiment, the surface treatment liquid used in the surface treatment of the glass cloth is filtered using an HDC II filter (manufactured by NIHON PALL LTD.). That is, first, the surface treatment liquid is passed through a filter having a mesh size of 10 μm, and then the surface treatment liquid is further passed through a filter having a mesh size of 4.5 μm. Thereby, aggregates possibly present in the surface treatment liquid are trapped. The filtered surface treatment liquid is used for the surface treatment of the glass cloth.
[0352] With respect to the glass cloth after the surface treatment, high-pressure opening is performed using a spray nozzle with a pressure of 3.5 kg / cm 2 . Subsequently, ultrasonic waves with a frequency of 25 kHz and an output power of 0.40 W / cm 2 are irradiated in water, whereby the glass cloth is further subjected to the opening treatment while reducing the excess silane coupling agent physically adhered to the glass cloth. Thereafter, drying is performed at 130°C for 1 minute. Through the above operation, the surface-treated glass cloth 2000 m is obtained.
[0353] (Example 2)
[0354] As the silane coupling agent, [4-[2-(trimethoxysilyl)ethyl]phenyl]methyl-2-propenoate (CAS NO: 141813-20-9, molecular weight = 310.42, silane coupling agent B) represented by the following formula is used, and otherwise, the glass cloth 2000 m is obtained by the same method as in Example 1.
[0355]
[0356] (Example 3)
[0357] As the silane coupling agent, 4-(trimethoxysilyl)phenyl-2-propenoate (CAS NO: 220369-00-6, molecular weight = 268.34, silane coupling agent C) represented by the following formula is used, and otherwise, the glass cloth 2000 m is obtained by the same method as in Example 1.
[0358]
[0359] (Example 4)
[0360] As the silane coupling agent, N-vinyl-N-(2-oxiranylmethyloxy)-3- (trimethoxysilyl)-1 -propanamine (CAS NO: 142177-48-8, molecular weight = 277.39, silane coupling agent D) represented by the following formula was used, and, other than this, glass cloth 2000 m was obtained by the same method as in Example 1.
[0361]
[0362] (Example 5)
[0363] As the silane coupling agent, 1 -vinyl-4-[3-(trimethoxysilyl)propoxy]benzene (CAS NO: 149738-31 -8, molecular weight = 282.41, silane coupling agent E) represented by the following formula was used, and, other than this, surface-treated glass cloth 2000 m was obtained by the same method as in Example 1.
[0364]
[0365] (Example 6)
[0366] As the silane coupling agent, 4-[2-(trimethoxysilyl)ethyl]aniline (CAS NO: 56926-97-7, molecular weight = 241.36, silane coupling agent F) represented by the following formula was used, and, other than this, surface-treated glass cloth 2000 m was obtained by the same method as in Example 1.
[0367]
[0368] (Example 7)
[0369] As the silane coupling agent, [bicyclo[2.2.1]hept-5-en-2-yl]triethoxysilane (CAS NO: 18401 -43-9, molecular weight = 256.41, silane coupling agent G) represented by the following formula was used, and, other than this, surface-treated glass cloth 2000 m was obtained by the same method as in Example 1.
[0370]
[0371] (Example 8)
[0372] Glass cloth Q was used instead of glass cloth P, and the silane coupling agent concentration in the surface treatment liquid was set to 0.25 mass%, and, other than this, glass cloth 2000 m was obtained by the same method as in Example 1.
[0373] (Example 9)
[0374] Glass cloth R was used instead of glass cloth P, and the concentration of the silane coupling agent in the surface treatment liquid was set to 0.25 mass%, and, except for this, glass cloth 2000 m was obtained by the same method as in Example 1.
[0375] (Example 10)
[0376] The surface treatment was performed without filtration of the surface treatment liquid, and, except for this, glass cloth 2000 m was obtained by the same method as in Example 1.
[0377] (Example 11)
[0378] Cooling of the surface treatment liquid was not performed even if the temperature of the surface treatment liquid exceeded 23°C, and bubbling of carbon dioxide was not performed even if the pH exceeded 4.0, and, except for this, glass cloth 2000 m was obtained by the same method as in Example 1.
[0379] (Example 12)
[0380] The concentration of the silane coupling agent in the surface treatment liquid was set to 0.75 mass%, and, except for this, glass cloth 2000 m was obtained by the same method as in Example 1.
[0381] (Example 13)
[0382] The concentration of the silane coupling agent in the surface treatment liquid was set to 1.1 mass%, and, except for this, glass cloth 2000 m was obtained by the same method as in Example 1.
[0383] (Comparative Example 1)
[0384] As the silane coupling agent, 3-(trimethoxysilyl)propyl-methacrylate (CAS NO: 2530-85-0, molecular weight = 248.35, silane coupling agent H) was used, and, except for this, surface-treated glass cloth 2000 m was obtained by the same method as in Example 1.
[0385] (Comparative Example 2)
[0386] As the silane coupling agent, 5-hexenyl-trimethoxysilane (CAS NO: 58751-56-7, molecular weight = 204.34, silane coupling agent I) was used, and, except for this, surface-treated glass cloth 2000 m was obtained by the same method as in Example 1.
[0387] (Example 14)
[0388] The surface treatment liquid was prepared by the above-described Production Method II, and the surface treatment of the glass cloth was performed without filtration of the surface treatment liquid, without cooling of the surface treatment liquid even if the temperature of the surface treatment liquid exceeded 23°C, without bubbling of carbon dioxide even if the pH exceeded 4.0, and otherwise, using the same method as in Example 1, to obtain 2000 m of glass cloth.
[0389] 〔Frequency of occurrence of white spots〕
[0390] In a roll-to-roll inspection stage, a tension of 100 N / 1300 mm was applied to the glass cloth while irradiating a halogen lamp, and the number of white spots in the glass cloth was counted for a length of 2000 m. Further, based on the inspection area and the number of white spots found in the inspection, the frequency of occurrence of white spots was calculated according to the following equation.
[0391] Frequency of occurrence of white spots (pieces / m 2 ) = Number of white spots / (Width of glass cloth (m) x Length of glass cloth for inspection (m))
[0392] Figure 1 is a photograph for explaining "white spots" in the present application. In this photograph, Figure 1 (a) of the photograph shows a portion having no white spots, and Figure 1 (b) of the photograph shows a portion having white spots P. In the present application, a white outline is observed by irradiation of a UV lamp, and the area enclosed by the outline (the area including the outline) is 0.8 cm 2 The above-described defect is defined as "white spots". Here, the outline is, for example, a circle. Note that the area enclosed by the outline is calculated by a known image analysis software.
[0393] 〔Example 1 of production of prepreg〕
[0394] In this production example 1, a polyphenylene ether resin was used as a raw material. That is, 45 parts by mass of polyphenylene ether (Noryl SA9000 manufactured by SABIC Corporation), 10 parts by mass of triallylisocyanurate, 45 parts by mass of toluene, and 0.6 parts by mass of 1,3-bis(tert-butylisopropylphenyl) were added to a stainless steel container, and stirred at room temperature for 1 hour. Thus, a varnish was prepared. After the glass cloth obtained in Examples 1 to 3, 5, 7, 8 to 14, and Comparative Examples 1 and 2 was impregnated in the prepared varnish, a prepreg was obtained after drying at 130°C for 1 minute.
[0395] 〔Example 2 of production of prepreg〕
[0396] In this Production Example 2, an epoxy resin was used as a raw material. That is, a clear varnish was prepared by compounding 80 parts by mass of a low-brominated bisphenol A type epoxy resin, 20 parts by mass of a cresol novolak type epoxy resin, 2 parts by mass of dicyandiamide, 0.2 parts by mass of 2-ethyl-4-methylimidazole, and 100 parts by mass of 2-methoxy-ethanol. After impregnating the glass cloth obtained in Examples 4 and 6 with the prepared clear varnish, a prepreg was obtained by drying at 130°C for 7 minutes.
[0397] [Production Example of Polyphenylene Ether Resin Substrate]
[0398] The obtained prepreg was sampled to a size of 20 cm x 20 cm. The obtained sample was overlapped by 8 pieces, and further, copper foils having a thickness of 12 μm were overlapped on the uppermost and lowermost sections thereof. Further, heating and pressurization were performed at 200°C, 40 kg / cm2for 120 minutes, whereby a resin substrate was produced. 2
[0399] [Production Example of Epoxy Resin Substrate]
[0400] The obtained prepreg was sampled to a size of 20 cm x 20 cm. The obtained sample was overlapped by 8 pieces, and further, copper foils having a thickness of 12 μm were overlapped on the uppermost and lowermost sections thereof. Further, heating and pressurization were performed at 195°C, 40 kg / cm2for 120 minutes, whereby a resin substrate was produced. 2
[0401] [Resistance to Welding Heat]
[0402] A laminate was obtained by removing the copper foils from the resin substrate. The obtained laminate was cut to a size of 5 cm x 5 cm to a total of 10 pieces. Thereafter, the laminate was heated at 133°C for 24 hours in a pressure cooker vessel and allowed to absorb water. Further, the laminate after absorbing water was immersed in a solder bath at 288°C for 20 seconds, whereby for the 10 pieces of laminate samples, the presence or absence of swelling due to peeling at the glass cloth / resin interface was visually confirmed, respectively.
[0403] The laminate sample in which swelling due to peeling at the glass cloth / resin interface was present was set to "not qualified", and the number of pieces of the "not qualified" laminate sample was recorded. The glass cloth having a smaller number of pieces recorded in the table means that the heat resistance is more excellent.
[0404] For the examples and comparative examples, the production conditions and evaluation results are shown in the following table. Note that the glass cloth of the examples can be used to produce a prepreg, a printed circuit board (resin substrate), an integrated circuit, and an electronic device by a conventional method.
[0405] [Table 1]
[0406]
[0407] [Table 2]
[0408]
[0409] According to Examples 1 to 14, it is possible to provide a glass cloth capable of achieving excellent dielectric properties, capable of suppressing the temporal increase in dielectric loss tangent, and capable of achieving excellent solder heat resistance for a resin substrate produced using the glass cloth. On the other hand, Comparative Examples 1 and 2 were not capable of suppressing the temporal increase in dielectric loss tangent.
[0410] Industrial Applicability
[0411] The present application can be utilized in fields related to glass cloth, printed circuit boards (particularly, printed circuit boards for high-speed communication), and the like.
Claims
1. A glass cloth which is constituted with a glass yarn containing a plurality of glass filaments as warp and weft, the glass cloth has a surface treatment agent on a surface, the surface treatment agent contains a silane coupling agent having a molecular structure with a value of 15.0 or less calculated from the following formula (A), 1.10 x MaxEStateIndex + 14.6 x MaxPartialCharge - 0.0917 x SPS + 2.47 x HallKierAlpha... (A).
2. The glass cloth of claim 1, wherein, White spots 10 / m 2 Below.
3. The glass cloth of claim 1 or 2, wherein, The content of silicon (Si) in the glass yarn is 95.0 to 100 mass% as calculated as silicon dioxide (SiO2).
4. The glass cloth according to claim 1 or 2, wherein, The silane coupling agent includes a silane coupling agent represented by the following general formula (1), X 4-n -Si-Y n …(1) In formula (1), X is each independently an organic functional group having at least one group selected from an epoxy group, an amino group, and an unsaturated double bond group having radical reactivity, Y is each independently an alkoxy group, and n is an integer of 1 or more and 3 or less.
5. The glass cloth of claim 4, wherein, X in the general formula (1) includes at least one group selected from the group consisting of an epoxy group, an amino group, an aromatic vinyl group, an acryloyl group, and a methacryloyl group.
6. The glass cloth of claim 1 or 2, wherein, The dielectric loss tangent of the glass cloth at 10 GHz is 0.002 or less.
7. The glass cloth according to claim 1 or 2, having a loss on ignition value in the range of 0.01 to 0.3 mass%.
8. The glass cloth of claim 1 or 2, wherein, The value calculated from the formula (A) is 14.4 or less.
9. The glass cloth of claim 1 or 2, wherein, The value calculated from the formula (A) is 13.8 or less.
10. The glass cloth of claim 1 or 2, wherein, The value calculated from the formula (A) is 13.5 or less.
11. The glass cloth of claim 1 or 2, wherein, White spots were 4 / m 2 Below.
12. The glass cloth of claim 1 or 2, wherein, White spots: 2 / m 2 Below.
13. The glass cloth of claim 1 or 2, wherein, White spots 0.1 / m 2 Below.
14. The glass cloth of claim 1 or 2, wherein, White spots 0.05 / m 2 Below.
15. The glass cloth of claim 1 or 2, wherein, The molecular weight of the silane coupling agent is in the range of 250 to 1000.
16. The glass cloth of claim 1 or 2, wherein, The molecular weight of the silane coupling agent is in the range of 300 to 750.
17. The glass cloth of claim 1 or 2, wherein, The molecular weight of the silane coupling agent is in the range of 350 to 700.
18. The glass cloth according to claim 1 or 2, which is used for a printed circuit board.
19. A prepreg containing the glass cloth according to claim 1 or 2, a matrix resin, and an inorganic filler.
20. A printed circuit board comprising the prepreg according to claim 19.
21. An integrated circuit comprising the printed circuit board according to claim 20.
22. An electronic device comprising the printed circuit board according to claim 20.
23. A method of manufacturing a glass cloth, wherein, The method includes: a step of weaving a glass cloth using a glass yarn including a plurality of glass filaments as warp and weft; and a step of performing surface treatment on the glass cloth using a surface treatment liquid containing a surface treatment agent after performing an oil removal treatment on the glass cloth, The surface treatment agent includes a silane coupling agent having a molecular structure with a value calculated from the following formula (A) of 15.0 or less, 1.10 x MaxEStateIndex + 14.6 x MaxPartialCharge - 0.0917 x SPS + 2.47 x HallKierAlpha... (A).
24. The method of manufacturing a glass cloth according to claim 23, wherein, The silane coupling agent includes a silane coupling agent represented by the following general formula (1), X 4-n -Si-Y n …(1) In formula (1), X is each independently an organic functional group having at least one group selected from an epoxy group, an amino group, and an unsaturated double bond group having radical reactivity, Y is each independently an alkoxy group, and n is an integer of 1 or more and 3 or less.
25. The glass cloth manufacturing method according to claim 23 or 24, wherein The surface treatment liquid is prepared by adding an acidic aqueous solution to a hydrolysis solution of the silane coupling agent.
26. The glass cloth manufacturing method according to claim 23 or 24, wherein The step of performing surface treatment includes: controlling the temperature and pH of the surface treatment liquid; and controlling the temperature and pH of the surface treatment liquid; and The surface treatment liquid is filtered.
27. The method of manufacturing a glass cloth according to claim 23 or 24, further comprising: The glass cloth is subjected to a fiber opening treatment after the surface treatment.
28. The method of manufacturing a glass cloth according to claim 23 or 24, further comprising: The white spots are inspected after the surface treatment.
29. A surface treatment liquid comprising a surface treatment agent containing a silane coupling agent, The silane coupling agent has a molecular structure having a value of 15.0 or less calculated from the following formula (A), 1.10 x MaxEStateIndex + 14.6 x MaxPartialCharge - 0.0917 x SPS + 2.47 x HallKierAlpha... (A).
30. The surface treatment liquid according to claim 29, wherein, The surface treatment liquid contains the silane coupling agent in a range of 0.20 to 1.2 mass% based on the total mass of the surface treatment liquid, The surface treatment liquid has a pH in a range of 2.5 to 5.5, The surface treatment liquid contains a surfactant in a range of 0.5 to 5.0 mass% based on the total mass of the silane coupling agent.
31. The surface treatment liquid according to claim 29 or 30, wherein, The silane coupling agent contains a silane coupling agent represented by the following general formula (1), X 4-n -Si-Y n …(1) In formula (1), each X is independently an organic functional group having at least one group selected from an epoxy group, an amino group, and an unsaturated double bond group having a radical reactivity, each Y is independently an alkoxy group, and n is an integer of 1 or more and 3 or less.
32. The surface treatment liquid according to claim 29 or 30, wherein, The value calculated from the formula (A) is 14.4 or less.
33. The surface treatment liquid according to claim 29 or 30, wherein, The value calculated from the formula (A) is 13.8 or less.
34. The surface treatment liquid according to claim 29 or 30, wherein, The value calculated from the formula (A) is 13.5 or less.
35. The surface treatment liquid according to claim 29 or 30, wherein, The surface treatment liquid has a pH in a range of 3.0 to 5.
0.
36. The surface treatment liquid according to claim 29 or 30, wherein The surface treatment liquid has a pH in a range of 3.0 to 4.
0.
37. The surface treatment liquid according to claim 29 or 30, wherein, The surface treatment liquid contains a surfactant in a range of 1.0 to 4.5 mass% based on the total mass of the silane coupling agent.
38. The surface treatment liquid according to claim 29 or 30, wherein, The surface treatment liquid contains a surfactant in a range of 1.5 to 4.0 mass% based on the total mass of the silane coupling agent.
Citation Information
Patent Citations
Glass cloth for low-dielectric material, and prepreg and printed wiring substrate using the same
JP2020194888A
Silica glass cloth, prepreg, and printed wiring substrate
JP2021063320A
Annealed quartz glass cloth and manufacturing method thereof
JP2021195689A
Prepreg, metal-clad laminate, and wiring board
WO2019065940A1
Prepreg, metal-clad laminate, and wiring board
WO2019065941A1